دور اختلاف الزمرة الدموية ABO بين الأم والجنين وحدوث الولادة الباكرة - الأيوب, جهاد (Latakia University Journal -Medical Sciences Series, 2019)
أجريت هذه الدراسة على 832 حامل في قسم التوليد بمشفى الأسد الجامعي باللاذقية في الفترة الواقعة ما بين 1/7/2006 و 1/7/2007. قسمت الحوامل حسب توافق أو اختلاف الزمرة الدموية مع وليدها إلى مجموعتين: المجموعة الأولى: وتضم الأمهات متوافقة الزمرة مع ولدانها وعددها 475 حالة. المجموعة الثانية: وتضم الأمهات مختلفة الزمرة مع ولدانها وعددها 357 حالة. كان هدف هذه الدراسة تحديد نسبة حدوث الولادة الباكرة في كل مجموعة. تبين لنا أن الولادة الباكرة حدثت عند 35 حامل في المجموعة الأولى أي بنسبة 7.36% مقابل 58 حامل في المجموعة الثانية أي ما نسبته 16.24%. This study was carried out on 832 pregnant women in the Obstetric and Gynecology Department at Al-Assad University Hospital in Lattakia between 1/7/2006 and 1/7/2007. They were divided into two groups: the first group included 475 cases showing ABO-compatibility of the blood of the mother and fetus. The second group consisted of 357 cases involving ABO-incompatibility of the blood of the mother and fetus. The purpose of this study was determine the premature delivery ratios for each group. The ratios of premature delivery in the first group were 7.36% versus 16.24% in the second group.